2018
DOI: 10.1002/fsn3.661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of component quality on sensory characteristics of a fish soup

Abstract: The foodservice industry is a highly competitive branch where customer satisfaction and loyalty is dependent on the price and the quality of the food. To improve cost competitiveness, instead of fresh ingredients, more preprocessed items are used as components in dishes. This may impair the perceived product quality, and thus potentially decrease customer satisfaction. The effects of the component quality on a single dish were tested by serving fish soup in a consumer study (n = 205), and by serving the dish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This process changes the physical characteristics of soup, forming large starch granules and leading to the loss of solids, color and proteins; even the initial vitamin content of the product is reduced during industrialization and storage. Similarly, the studies by Kumpulainen, Sandell and Hopia (2018) have shown how the processed elements in these products cause product losses.…”
Section: Introductionmentioning
confidence: 88%
“…This process changes the physical characteristics of soup, forming large starch granules and leading to the loss of solids, color and proteins; even the initial vitamin content of the product is reduced during industrialization and storage. Similarly, the studies by Kumpulainen, Sandell and Hopia (2018) have shown how the processed elements in these products cause product losses.…”
Section: Introductionmentioning
confidence: 88%
“…Quantitative descriptive sensory analysis was applied to evaluate crucian carp soups prepared in stewpot with different heating modes. The sensory evaluation took place in a sensory laboratory which was designed in accordance with international standards ISO 8589:2007 20 . The panel consisted of 15 members (8 females and 7 males, aged 20‐45) selected and trained according to international standards.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the different components in the final sensory characteristics of the starter soups was interpreted by reducing the number of variables into two principal components, as found by Kumpulainen, Sandell, and Hopia (2018). The number of sensory attributes changes at conventional and salt reduction foods can differ across dishes due to flavor interactions and/or ingredient changes required Nguyen and Wismer (2019).…”
Section: Acceptability and Saltiness Perceptionmentioning
confidence: 99%